Green synthesis of silver nanoparticles using Hagenia abyssinica (Bruce) J.F. Gmel plant leaf extract and their antibacterial and anti-oxidant activities - Walelign Wubet Melkamu (Elsevier, 2021)
Green synthesis of silver nanoparticles (AgNPs) was achieved by bio-reduction of silver nitrate using Hagenia Abyssinica plant leaf extract (HAPLE). The AgNPs formation was confirmed by Ultraviolet-Visible (UV-Vis) spectrophotometer. The synthesized AgNPs in solution have shown maximum absorption at 430 nm. The different parameters like temperature, pH, time, silver nitrate concentration and volume of leaf extract were optimized spectrophotometrically. The Fourier-Transform Infrared (FTIR) Spectroscopy was used to confirm the existence of various functional groups responsible for reducing and stabilizing during the biosynthesis process. The X-Ray Diffraction (XRD) analysis confirmed the structure, crystal size and nature of the AgNPs. The synthesized AgNPs showed antimicrobial (gram-negative bacteria (klebsiella pneumoniae and salmonella typhimurium) and gram-positive bacteria (Streptococcus pneumoniae)) and antioxidant (2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging method) activities. The developed method for the AgNPs synthesis using HAPLE is an eco-friendly and convenient method. In near future, the synthesized AgNPs could be used in the fields of water treatment, biomedicine, biosensor and nanotechnology.